THE EFFECT OF NICKEL-COBALT CONCENTRATION RATIO ON THE PERFORMANCE OF NICKEL COBALT HYDROGEN PHOSPHATE AS A SUPERCAPACITOR ELECTRODE - Ubaidillah, Achmad
Supercapacitors are energy storage components that have a short charging time and a large power capacity. The performance of the supercapacitor itself is closely related to its capacitance. Supercapacitor capacitance is affected by several values such as electrode surface area, dielectric distance, and materials used. Based on that, the selection of supercapacitor electrodes using nickel cobalt hydrogen phosphate is carried out which is known to have potential based on previous research. This study was conducted to test the capacitance of nickel cobalt hydrogen phosphate material by varying the concentration ratio of nickel and cobalt in it to determine its effect on supercapacitor capacitance. Based on the experiments, it is known that supercapacitor electrodes made from nickel cobalt hydrogen phosphate material have the potential to be used as supercapacitor electrodes. In addition, the ratio of nickel-cobalt concentrations affects the specific capacitance value of nickel cobalt hydrogen phosphate. From various concentration variations, it is known that nickel cobalt hydrogen phosphate with a nickel-cobalt concentration ratio of 5:1 has the largest capacitance with a specific capacitance value of 279 F/g.